Lyric address in Dutch literature, 1250-1800 - Haven, Cornelis van der 1978-; Pieters, Jürgen 1969- (Amsterdam University Press, 2018)
In their accessible analysis, these preeminent translations of ten canonical Dutch poems discuss each poem's historical context, revealing its political or ideological framing, religious elements, or the self-representational interests of the poet. The book focuses on how the use of the speaker's "I" creates distance or proximity to the social context of the time. Close, detailed analysis of rhetorical techniques, such as the use of the apostrophe, illuminates the ways in which poetry reveals tensions in society.
Keywords: Geschichte 1250-1800; Rhetorik; Niederländisch; Zeithintergrund; Erzählsituation; Adressat; Lyrik; Dutch poetry / Criticism and interpretation; Dutch poetry; Criticism, interpretation, etc; Aufsatzsammlung